Post-divorce parental conflict, maternal economic hardship, parent-child relationship and academic achievement among adolescents in divorced families - Esmaeili, Nooshin Sabour; Yaacob, Siti Nor (Iceland Glaciological Society, 2013)
The purpose of this study was to determine the relationships between post-divorce parental conflict, maternal economic hardship and parent-child relationship with academic achievement in a sample of 800 adolescents of divorced families aged 15to 18 years old using probability proportionate to size sampling technique. The findings indicated that post-divorce parental conflict, maternal economic hardship and parent-child relationship were associated with academic achievement among adolescents of divorced families. The findings implied that adolescents who experienced high level of post-divorce parental conflict, high maternal economic hardship and poor parent-child relationship tend to exhibit lower level of academic achievement. The present study concludes that parent-child relationship is the strongest predictor of academic achievement among adolescents of divorced families in Mashhad/Iran.